PENETAPAN HARGA TOKO SEMBAKO DI DUSUN SUMBERURIP DESA BARUREJO KECAMATAN SILIRAGUNG KABUPATEN BANYUWANGI DALAM PERSPEKTIF EKONOMI ISLAM - Munawir; Imam Husnudin; Zainudin Fanani (ICO EDUSHA, 2021)
Abstrack The objectives of this study include: 1) Knowing and analyzing the price fixing for basic food shops in Sumberurip Hamlet, Barurejo Village, Siliragung District, Banyuwangi Regency. 2) Knowing and analyzing the suitability between the price fixing for the basic food shops in Sumberurip Hamlet, Barurejo Village, Siliragung District, Banyuwangi Regency with the Islamic Economic Perspective. This study uses a qualitative research method with the type of case study research that is single case design (single case design). The conclusions in this study are, 1) Determination of the price of basic necessities at the Sumberurip hamlet shop, Barurejo Village, Siliragung District, Banyuwangi Regency, is a price setting based on demand made by buyers, based on profits, the price set can still change every day, can still bargain according to the agreement of both parties. Based on competition, usually also use the price circulating in the market. 2) The determination of the price of basic necessities is carried out in Sumberurip Hamlet, Barurejo Village, Siliragung District, Banyuwangi Regency if it is contextualized from an Islamic economic perspective in general, it is in accordance with the Islamic Economic Perspective. This can be seen from the pricing based on a fair price that is in accordance with the Islamic Economic Perspective. Keywords: Determination, Price, Basic Food, Islamic Economic Perspective Referensi Abdullah M. 2014. Metode Penelitian Ekonomi Islam(Muamalah). Bandung: Pustaka Setia. Afzalurahman Muhammad. 2012. Ensyklopedia Search Terjemahan Dewi Nurzalin Dkk. Muhammad Sebagai Pedagang Jakarta: Penebar Swadaya. Al - Qardawi, Yusuf. 2010. Norma dan Etika Dalam Ekonomi Islam. Jakarta: Gemma Isnani. Amalia, Euis. 2010. Sejarah Pemikiran Ekonomi Islam. Jakarta: Gramata Publishing. Basu Swasta, Dharmesta dan Irawan, 2008. Manajemen Pemasaran Modern. Liberty, Yogyakarta. Basu Swastha Dharmmesta, T. Hani Handoko, 2004. Manajemen Pemasaran Analisa perilaku konsumen . Edisi pertama cetakan ketiga. BPFEYogyakarta, Yogyakarta. Chamid, Nur. 2010. Jejak Langkah Sejarah Pemikiran Ekonomi Islam. Yogyakarta: Pustaka Pelajar. Cholil Umam, Taudlikhul Afkar, 2009. Modul Kewirausahaan Untuk Mahasiswa dan Umum. Surabaya : IAIN Sunan Ampel Press Departemen Agama RI, Q.S Hud (11): 58. Al-Baqarah (2): 278 dan An-Nisa (4):29. Idris Parakkasi Dan Kamiruddin, 2018. Analisis Harga Dan Mekanisme Pasar Dalam Perspektif Islam. Hakim, Lukman. 2012. Prinsip-PrinsipEkonomi Islam. Surakarta : Erlangga. Hamid, Abu Muhammad. 2013. bin Muhammad bin Ahmad Al-Ghazali Al-Tussi, IhyaUlumudin, Cet 4, Semarang: CV. Asy – Syifa. Irsad.Z, Marketing Mix Mempengaruhi Kepuasan Pelanggan. Di unduh pada Tanggal 23 Februari 2016. Islahi, A.A. 2014. Konsep Ekonomi Ibnu Taimiyah, Anshari Thayib. Jakarta: PT Bina Ilmu Offset, Abu Muhammad Hamid, bin Muhammad bin Ahmad Al-Ghazali Al-Tussi, 2013. IhyaUlumudin, Cet 4, Semarang: CV. Asy – Syifa. Karim, Adiwarman Aazwar. 2004. Sejarah Pemikiran Ekonomi Islam. Ed 3. Cet. Ke-2, Jakarta: PT Raja Gravindo Persada. Karim, Adiwarman. 2003. Ekonomi Mikro Islam. Jakarta:Penerbit III T Indonesi. Kendro Pratomo, 2018. Mekanisme Pasar Dan Penetapan Harga Dalam Perekonomian Islam (Studi Analisis Pemikiran Ibn Taimiyah). Kotler, P., & susanto, A. B. 2000. Manajemen Pemasaran di Indonesia Analisis, Perencanaan, Implementasi dan Pengendalian. Jakarta : Selemba Empat. Moleong, Lexy j. 2002. Metode Penelitian Kualitatif. Bandung: PT Remaja Rosdakarya Moleong, Lexy j. 2011. Metode Penelitian Kualitatif. Bandung: PT Remaja Rosdakarya Muhammad, 2004. Ekonomi Mikro dalam persfektif Islam. Cet. Ke-1, (Yogyakarta: BPFE. Mujahidin, Akhmad. 2014. Ekonomi Islam. Jakarta: Raja Grafindo Persada. Nasution, Mustafa Edwin, dkk. 2017. Pengenalan Eksklusif : Ekonomi Islam. Depok: Kencana.Rozalinda. 2017. Ekonomi Islam. Depok: Rajawali Pers.Supriyatno. 2008. Ekonomi Mikro Perspektif Islam. Malang: UIN Malang Pers. Nur Ika Mauliyah, 2018. Strategi Penentuan Harga Jual Sayuran Pada Pedagang Pasar Tradisional (Studi Fenomenologi Pedagang Sayur Di Blitar). Profil Desa Barurejo 23 Juni 2021 Putong, Iskandar. 2000. Pengantar Ilmu Mikro & Makro. cetakan pertama, Jakarta: Ghalia Indonesia. Rambat dan Hamdni. 2008. Ekonomi Manajerial. edisi ke 1, Bandung: Remaja Rodakarya. Rosmizal. 2011. Mekanisme penetapan harga jual ayam pedagang (brotler) ditinjau dari perspektif ekonomi islam (studi kasus PT. Sumatera Mitra Mandiri Pekanbaru). Rusli dan Qaderie. 2013. Metode Penelitian Kuantitatif dan Kualitatif. Sumenep:LP3M “Paramadani”Preduan Sigit, Suhardi. 2000. Manajemen Pemasaran. Yogyakarta: UTS. Sudarsono, Heri. 2004. Konsep Ekonomi Islam. Yogyakarta: Ekonosia. Sudaryono. 2016. Manajemen Pemasaran Teori Dan Implementasi. Yogyakarta: ANDI Sugiyono, 2015. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung:Alpabeda. Sunyoto, Danang. 2013. Ekonomi Manajerial Konsep Terapan Bisnis. Jakarta: CAPS (Center Academic Publishing Service. Syafei Racman, 2000. Fiqih Muamalah. Bandung : Pustaka Setia. Tim Reality. 2008. Kamus Terbaru Bahasa Indonesia Dilengkapi Ejaan Yang Benar. Jakarta: PT. Reality Publisher. Yin, Robert, K. 2014. Studi Kasus desain & medote. Jakarta:PT. Raja Grafindo Persada.